A miniature dual‐band Wilkinson power divider using novel planar transmission line. Issue 2 (14th July 2020) - Li, Yansheng; Wu, Mi; Chung, Kwok L.; Feng, Botao
Abstract: This article presents a miniaturized Wilkinson power divider (WPD) for dual‐band applications using a novel planar transmission line. The new planar line fully uses the substrate area and aims to take place of the quarter‐wave transformers of the traditional WPD. Namely, the copper foil on the both sides of the substrate were used to composite microstrip line (ML) and a coplanar waveguide (CPW) line. The transitions of the ML and CPW were achieved by a copper via. The WPD has realized a miniaturization at 0.9 and 2.9 GHz with a small footprint of 12.92 × 6.8 mm 2 .The simulated results are verified by measured results to show that the isolations within the dual band are both less than −20 dB, the reflection coefficients are both less than −10 dB, whereas the insertion loss are both less than 3.10 dB in 0.8 to 1.0 GHz and 2.8 to 3.0 GHz bands.